Bioremoval of Co(II) by a novel halotolerant microalgae Dunaliella sp. FACHB-558 from saltwater - Liu, Chenglong; Wen, Xueer; Pan, Huiqiao; Luo, Ying; Zhou, Junyang; Wu, Yuzhe; Zeng, Zhiyong; Sun, Ting; Chen, Jun; Hu, Zhangli; Lou, Sulin; Li, Hui (Frontiers in Microbiology, 2024)
Cobalt pollution is harmful to both the aquatic ecosystem and human health. As the primary producer of aquatic ecosystems in hypersaline environments, unicellular planktonic Dunaliella microalgae is considered to be a low-energy and eco-friendly biosorbent that removes excess cobalt and enhances the vitality of coastal and marine ecosystems. In this study, we found that the halotolerant microalga named Dunaliella sp. FACHB-558 could grow under a salinity condition with 0.5–4.5 M NaCl. A phylogenetic analysis based on the rbcL gene revealed that Dunaliella sp. FACHB-558 is a close relative of Dunaliella primolecta TS-3. At lab-scale culture, Dunaliella sp. FACHB-558 exhibited high tolerance to heavy metal stresses, including cobalt, nickel, and cadmium. Treatment with 60 μM cobalt delayed its stationary phase but ultimately led to a higher population density. Furthermore, Dunaliella sp. FACHB-558 has the ability to adsorb the cobalt ions in the aquatic environment, which was evidenced by the decreased amount of cobalt in the culture medium. In addition, the tolerance of Dunaliella sp. FACHB-558 to cobalt stress was correlated with enhanced nitric oxide content and peroxidase activity. The autophagy inhibitor 3-MA enhanced nitric oxide burst, increased peroxidase activity, and accelerated the bioremoval of cobalt, suggesting that the autophagy pathway played a negative role in response to cobalt stress in Dunaliella sp. FACHB-558. In summary, our study identified a novel microalga possessing high cobalt tolerance and provided a promising natural biosorbent for the research and application of heavy metal bioremediation technology.